EFEKTIVITAS APLIKASI INVENTOR SEBAGAI MEDIA PEMBELAJARAN PEMAHAMAN HURUF HIRAGANA PADA SISWA KELAS XII SMK NEGERI 7 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The Inventor application is a simple software from the android operating system that functions to produce a medium for a particular job, one of which is as a learning medium for students to understand hiragana letters in Japanese. The purpose of this study was to determine the effectiveness of using the Inventor application as a learning medium for understanding hiragana letters in class XII students of SMK Negeri 7 Pekanbaru. The sample in this study consisted of 20 students in the Accounting class as the experimental class and 20 students in the Multimedia class as the control class. The method used in this research is experimental quantitative. From the results of data analysis on students in the experimental class using SPSS version 25 software, it shows that the Inventor Application can improve students' ability to understand hiragana letters with an average value in the very high category.Key Words: Hiragana, Learning media, Inventor application